2012
DOI: 10.1016/j.ydbio.2011.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial coding of Drosophila muscle shape by Collier and Nautilus

Abstract: The diversity of Drosophila muscles correlates with the expression of combinations of identity transcription factors (iTFs) in muscle progenitors. Here, we address the question of when and how a combinatorial code is translated into muscle specific properties, by studying the roles of the Collier and Nautilus iTFs that are expressed in partly overlapping subsets of muscle progenitors. We show that the three dorso-lateral (DL) progenitors which express Nautilus and Collier are specified in a fixed temporal sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 60 publications
3
50
0
Order By: Relevance
“…Besides the support of haemocytes, collier is also required for the formation of the dorsal/acute 3 (DA3) embryonic muscle, which does not develop in its absence 46,47 . Together with nautilus, the only homologue of MRF bHLH factors in Drosophila, collier controls shape and morphology of the DA3 muscle 48 . Here we report that Ebf3 is required for the relaxation of the diaphragm and that it synergises with MyoD in inducing a critical cell-type specific gene.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the support of haemocytes, collier is also required for the formation of the dorsal/acute 3 (DA3) embryonic muscle, which does not develop in its absence 46,47 . Together with nautilus, the only homologue of MRF bHLH factors in Drosophila, collier controls shape and morphology of the DA3 muscle 48 . Here we report that Ebf3 is required for the relaxation of the diaphragm and that it synergises with MyoD in inducing a critical cell-type specific gene.…”
Section: Discussionmentioning
confidence: 99%
“…Stripe-GAL4 flies were provided by G. Morata (CBMSO, Universidad Autonoma de Madrid, Madrid, Spain). Collier-GFP flies were a gift from Dr Alan Vincent (Centre de Biologie du Développement, UMR 5547 and IFR 109, CNRS and Université Paul Sabatier) (Dubois et al, 2007;Enriquez et al, 2012). Homozygous embryos were recognized by the lack of either CyO,YFP or CyO,Wg-lacZ.…”
Section: Fly Strainsmentioning
confidence: 99%
“…As muscle identity is conferred by activation of specific combinations of iTFs in each PC, we looked at Tup expression at the PC stage. As general marker of PCs/FCs, we used rp298lacZ (Beckett and Baylies, 2007;Enriquez et al, 2012;Nose et al, 1998). Staining of late stage 11 rp298lacZ embryos for lacZ and either Tup or Col, showed that Tup expression is expressed in the four dorsal-most PCs ( Fig.…”
Section: Tup: a New Muscle Identity Transcription Factormentioning
confidence: 99%